Korean Industrialization, Skill Demand, and Wage Premium - Lee, Changkeun (KDI School of Public Policy and Management, 2020)
This paper aims to observe the evolution of skilled labor demand and relative wages during the rapid industrialization period. Although this historic episode has attracted the researchers’ attention, the evolution of skill demand and its impact on inequality remained as a black box. To provide first-hand evidence, I construct a 3-digit industry-level dataset that covers 1955-1980 from the Mining and Manufacturing survey. Then I measure skill demand and relative wages following the skill-biased technological change literature. Analysis results show that Korea experiences drastic skill upgrading during its rapid industrialization. The nonproduction workers’ share in wage bill increased throughout the 25 years of 1955-1980. Relative demand rose much faster in industries that were initially less skill-intensive but accumulated capital through investment faster. This implies that there was a strong skill-capital complementarity. Increasing skill demand and skill-capital complementarity are a force of increasing skill premium in wages and wage inequality. It was so until 1973. However, since then relative wages fell while skill demand kept rising. This is unique to the Korean experience, It also implies that the supply of skilled labor expanded even faster than the skill demand. Although it is possible to connect this to the heavy-chemical industrialization, falling skill premium and inequality was most driven by the “within” or common effect. Furthermore, emerging heavy-chemical industries had greater skill demand, therefore a positive effect on relative wage.